PENGGUNAAN MODEL PEMBELAJARAN KONTEKSTUAL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KETERAMPILAN DI KELAS VIIIC SMP PEMBANGUNAN LABORATORIUM UNP - HARRY PRASETYO, Drs. Yusron Wikarya, M.Pd. Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2016)
The purpose of this study is to promote creativity and student learning outcomes in subjects skill in the class VIIIC Junior High School Pembangunan Laboratorium UNP using contextual learning model. The experiment was conducted using classroom action research. Methods and means of collecting datain this study is the observation format of student creativity, questionnaires and tests the creativity of students learning outcomes. The results obtained by the processing of data showing an increase in creativity and student learningoutcomes. Creativity In the first cycle of 57.34% less criteria, the second cycle students' creativity criteria were 71.92%, 84.77% the third cycle of creativity high criteria. student learning outcomes pre-cycle average of 70.29 into 78.63 in thefirst cycle, the second cycle average 80.66 and third cycle average of 81.33. Based on the findings of the above study concluded that contextual learning model can enhance the creativity and skill of learning outcomes in the classroom VIIIC in the Junior High School Pembangunan Laboratorium UNP.Kata Kunci : Kreativitas, Hasil Belajar, Model Pembelajaran Kontekstual.